2016
DOI: 10.1007/s11090-016-9717-2
|View full text |Cite
|
Sign up to set email alerts
|

PMMA Surface Functionalization Using Atmospheric Pressure Plasma for Development of Plasmonically Active Polymer Optical Fiber Probes

Abstract: In this paper, we demonstrate the development of plasmonically active PMMA optical fiber probes by the attachment of gold nanoparticles to the probe surface functionalized by means of flowing post-discharges from dielectric barrier discharge (DBD) plasmas for the first time. Polymer optical fiber (POF) probes (U shape to improve absorbance sensitivity) were subjected to reactive gas atmospheres in the post-discharge region of a coaxial DBD plasma reactor run at atmospheric pressure in different gases (Ar, Ar ?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…In a different study, UV irradiation has been reported to generate carbonyl groups on a PMMA‐POF surface by Nugen et al., (2009) . Recently, our group has demonstrated the argon plasma treatment‐based functionalization of POF . Although many of these physical and chemical methods are efficient enough to functionalize the PMMA surface, most of these suffer from poor chemical reactivity, low surface energy, presence of weak cohesive layer and large batch to batch variations .…”
Section: Introductionmentioning
confidence: 97%
“…In a different study, UV irradiation has been reported to generate carbonyl groups on a PMMA‐POF surface by Nugen et al., (2009) . Recently, our group has demonstrated the argon plasma treatment‐based functionalization of POF . Although many of these physical and chemical methods are efficient enough to functionalize the PMMA surface, most of these suffer from poor chemical reactivity, low surface energy, presence of weak cohesive layer and large batch to batch variations .…”
Section: Introductionmentioning
confidence: 97%
“…Within the context of polymer materials, plasma processing has been widely used for, among others, polymerizing gaseous monomers, [2] promoting the grafting of other nano-or microstructured polymeric components, [3,4] cleaning and etching surfaces, [5] sterilizing and disinfecting, [6] and functionalizing surfaces. [7] Among the different applications of polymers processed with plasma technologies, the fabrication of advanced biomedical sensors for electrochemical detection is gaining attention. [8] Electrochemical sensors are devices that provide real-time information on the composition of a system by connecting an (electro) chemically selective coating layer, which is typically made of a conducting or an electroresponsive material, to an electrochemical transducer (also named electrode).…”
Section: Introductionmentioning
confidence: 99%
“…Within the context of polymer materials, plasma processing has been widely used for, among others, polymerizing gaseous monomers, [ 2 ] promoting the grafting of other nano‐ or microstructured polymeric components, [ 3,4 ] cleaning and etching surfaces, [ 5 ] sterilizing and disinfecting, [ 6 ] and functionalizing surfaces. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Плазмохимическая модификация не требует применения химических реагентов и является экологически чистой технологией, а также позволяет обрабатывать полимерные материалы практически любого вида и формы [10,11]. При этом меняются только поверхностные свойства полимерного протеза, так как модификации подвергается приповерхностный слой толщиной приблизительно 10 нм [12,13], а механические и физикохимические параметры самого протеза остаются прежними.…”
Section: Introductionunclassified